KINERJA CAMPURAN HOT ROLLED ASPHALT DENGAN VARIASI FILTER YANG DIPADATKAN DENGAN GYRATORY TESTING MACHIN - Jazir, Muhammad
The research renewed appication of a new test method developed in early 2000 by Departement of Public Work especially Percentage of Refusal Density Method (DPU-2000). Some adjustments to ARRB's and SHRP's researches was also done here. Generally, this research touched some important aspecs of level one and level two of SHRP's or ARRB's research, and a new methoc of DPU-2000 application here used gyratory testing machine. This research also includes a review on HRA F No. 10 (40/10) compacted by gyratory with the usage of some fillers eg : stone dust, fly ash, burntbrick and porland cement. The main tests for mixtures performed, were : Marshall Test, Marshall Immersion Test and wheel tracking test. Other things estimated were deformation resistant prediction with gyratory and mixtures workability identification based on compaction index (CI) and workability index (WI) that calculated from gyratory compaction data. Compaction characteristics using gyratory are : mould diameter 100 mm, pressure 240 kPa, angle 2Â° and speed of gyration 60 rpm. Refusal gyration was done at Nmax=Nref=350 rotations and design gyration at Ndes=120 rotations. All of briquettes have been compacted at Nmax or Ndes, were also tested using Marshall Test and Marshall Immersion Test. The research results show that mixtures containing filler such as portland cement, stone dust and fly ash able to satisfy mixtures criteria of DPU-2000. The best performance was presented by cement filler with a very good result on wheel tracking test. And second rank was stone dust, with high deformation resistant and a good workability (particularly CI). Next one is containing fly ash filler with a good Marshall Properties, satisfaction volumetric characteristics, and also shows a highest Marshall Retained Stability Index. But low value on workability (particularly CI) and deformation resistant cause that mixture is not classified as a better one. Finally burntbrick filler that is able to achieve Marshall Properties and Marshall Retained Stability Index specification, but its volumetric criteria, workability (especially WI) and rutting occurs at wheel tracking test shows bad result. And therefore it does not suggest to use burntbrick as a filler